Pengaruh Inovasi Pelayanan Terhadap Nilai Pelanggan Melalui Keunggulan Kompetetif Bank - Haris, Abdul (Insan Cita Bongaya Research Journal, 2022)
This study aims to examine the effect of service innovation on Bank Sulsesl customers through competitive advantage in Makassar City. The research sample was 100 respondents. The results of the study show that the service innovation played by South Sulawesi banks is currently getting value from customers. Because customers feel good service and different from competitors, so this service becomes top of mind in the customer's head. In fact, the South Sulawesi bank became part of the main choice. In other words, service innovation will get value from customers. Service innovation will mean being equipped with a customer's competitive advantage so that it will provide value as well as become a priority for customers. Then, the limitation of the study is that the research was only conducted on South Sulawesi banks so that the findings produced have limitations in terms of the ability to generalize the research findings to other banking companies, such as state and private foreign exchange banks. This study aims to examine the effect of service innovation on Bank Sulsesl customers through competitive advantage in Makassar City. The research sample was 100 respondents. The results of the study show that the service innovation played by South Sulawesi banks is currently getting value from customers. Because customers feel good service and different from competitors, so this service becomes top of mind in the customer's head. In fact, the South Sulawesi bank became part of the main choice. In other words, service innovation will get value from customers. Service innovation will mean being equipped with a customer's competitive advantage so that it will provide value as well as become a priority for customers. Then, the limitation of the study is that the research was only conducted on South Sulawesi banks so that the findings produced have limitations in terms of the ability to generalize the research findings to other banking companies, such as state and private foreign exchange banks.